Znaczenie wybranych miast dla rozwoju obszarów przygranicznych - Rączaszek, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The study points at the significance of big cities for the level of regional development. The area of research covered the territories close to the country's border. Regardless of the means of identification of the borderland there are big cities belonging to these areas. The question of the settlement network of the country was also taken into account in the introduction to the analysis. The spatial development's level was based on the analysis of the measures. Another set of measures (15) was applied to examine the frontier communes and another one (20) to examine the administrative districts contiguous to the country's border. The set of measures was forced by the GUS's mode of data publication for the units of administrative division of the country. These publications for communes and administrative districts do not always refer to the same issues. Within the border area there were 20 cities identified of 36 - 460 thousand inhabitants. These cities emerge in the discussion of the levels of the particular measures, when the extreme values are being discussed. Big cities then unambiguously influence the assessment of the social development' s level of examined areas. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 59-85